SUBSTANTIATION OF THE METHOD OF COMPLEX ASSESSMENT OF ENERGY-ECOLOGICAL-ECONOMIC EFFICIENCY OF ENERGY SUPPLY SYSTEMS WITH COGENERATION HEAT PUMP INSTALLATIONS AND PEAK SOURCES OF HEAT - Olga, Ostapenko (Scientific Works of Vinnytsia National Technical University, 2018)
Substantiation of the method of complex assessment of energy-ecological-economic efficiency of energy supply systems (ESS) with cogeneration heat pump installations (CHPI) and peak sources of heat (PSH), that has in-depth approach to the assessment of energy transformations in the elements of ESS has been performed, it enables to provide the substantiated determination of high energy efficient, ecologically safe and economically substantiated operation modes of ESS with CHPI and PSH on conditions of variable: operation modes of ESS and its elements, levels of ESS elements energy efficiency, refrigerants, sources of drive energy and topological composition of ESS.